Prevalence of human papillomavirus genotypes in Latvia among women participating in cervical cancer screening - Stasulane, Anna; Grundmane, Justine; Sulte, Kristiana; Stasulans, Janis; Cernavska, Solvita; Smite, Laura (Frontiers in Oncology, 2025)
Background and objectivesThe propensity of human papillomavirus (HPV) to cause cervical cancer is linked to specific genotypes that vary in carcinogenicity. This study aims to provide insight into the most prevalent HPV genotypes in Latvia among women participating in cervical cancer screening.Materials and methodsThe prevalence data presented in this study were derived from routine screening. The data were collected during the first two years of the reorganized screening program, from 1 July 2022 to 1 July 2024, which for the first time included HPV genotyping as a primary screening method in women aged 30–70. Testing was performed in an accredited laboratory using a commercial kit capable of detecting 14 HPV genotypes.ResultsThe overall prevalence among 30–70-year-old women participating in cervical cancer screening in Latvia was 12.04%. HPV 16 was the most prevalent HPV genotype, followed by HPV 68, 31, 66, 52, 56, 51, 45, 33, 39, 18, 58, 59, and 35. Across all age categories, single infections were the most prevalent—81.82% of women tested positive for only one HPV genotype, with an average of 1.23 genotypes per positive sample. The prevalence of both single and co- infections tended to decrease with age, except for a slight increase in the oldest age group, women aged 60–70. There was a significant difference in the overall HPV infection prevalence across age groups.ConclusionsThese results provide valuable epidemiological data that can inform cervical cancer screening, prognosis, HPV vaccine implementation targeting region-specific genotypes, and ongoing monitoring of genotype distribution.